The Role of Business Strategy in the Implementation of Corporate Social Responsibility in the Energy Sector - Dini Primasari Priadi; Kurniawati Kurniawati (Journal of Social Research, 2025)
The energy sector requires strong integration between business strategy and Corporate Social Responsibility (CSR), especially to maintain competitiveness in the shift toward clean and sustainable energy. This study aims to analyze how business strategy influences CSR implementation in Indonesia’s energy industry, focusing on the role of business development, corporate actions, and leadership support across subsectors such as oil and gas, minerals and coal, electricity, geothermal, renewable energy, bioenergy, and energy conservation. Using a qualitative approach with in-depth interviews, data were collected from respondents involved in strategic planning and CSR in energy companies. The findings show that business strategy has a significant positive influence on CSR practices; however, strategic integration remains weak due to limited managerial awareness of CSR’s potential to create competitiveness, strengthen reputation, and build stakeholder trust. Companies still prioritize operational and financial performance over sustainability initiatives. Practically, the study highlights the need to align CSR with national priorities and global sustainability trends, supporting market positioning and long-term value creation. Strengthening sustainability-oriented innovation, clean energy development, and community-based CSR programs can enhance competitive advantage. Leadership support is crucial in embedding CSR into business strategy and organizational culture, enabling differentiation and success in Indonesia’s evolving energy market.